UMPSA Recognised as the Best Technology University for Sustainability in Malaysia, Ranked 62nd Globally - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 20 December 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to excel as the best technology university in Malaysia, achieving 62nd place globally in the UI GreenMetric World University Rankings (UIGWUR) 2024, recently announced by UI GreenMetric.